Cost-Oriented Open Source Automation Potential Application in Industrial Control Applications. Issue 29 (2016) - Hoxha, Valmir; Bula, Ines; Shala, Muzafer; Hajrizi, Edmond
Abstract: One of the most cost effective ways to make system control (automation) is by using open source hardware and software, in order to be cost oriented besides the price the systems need to be implemented in reasonable time frame and also needs to be reliable and safe. In this paper we will treat and justify the cases of using the Open Source Hardware and Software, in comparison to industry standard Programmable Logic Controllers (PLC). Also we will discuss about the point of system complexity where the cost reduction will not justify the time spend to build the interfacing of sensors, digital and analog I/O for the open source Hardware.